(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This paper presents a methodology for teaching series and parallel circuit connections in schools using the PhET simulation program. The approach integrates interactive simulations to enhance students’ conceptual understanding and problem-solving skills. By utilizing virtual experiments, students can visualize electrical current flow, resistance distribution, and voltage changes in real-time, making abstract concepts more tangible. The methodology also incorporates inquiry-based learning strategies, allowing students to explore, hypothesize, and verify their findings through guided activities. The effectiveness of this approach is discussed in terms of engagement, comprehension, and retention of circuit theory concepts.